Phytochemistry and Biological Properties of Aristotelia Chilensis a Chilean Blackberry: A Review - Zuniga-Navarro, G; Contreras-Arredondo, R (Springer Netherlands, 2017)
Aristotelia chilensis (Mol.) Stuntz, commonly called Maqui, is known for its pharmacological uses in traditional medicine of native Mapuche communities in Chile. It is reported to have excellent medicinal properties that help to cure chronic diarrhea, dysentery, throat diseases, intestinal tumors, fever, wounds healing, and scars. Pharmacologically, fruits and leaves of Maqui have been investigated for antioxidant, antidiabetic, and antiviral activities. The current high demand of natural antioxidants has placed Maqui as one of the most over-exploited species in Chile. This review analyzes the information collected from the published research articles, and highlights the phytochemical and pharmacological aspects of A. chilensis. The information will be useful to develop new strategies of sustainable use of the species to generate new formulations with therapeutic and economical value in the future. © 2017, Springer Science+Business Media B.V.